Analysis of the Role of Social Media in E-Government Implementation: A Meta-Analysis Study - Aji Machmud, Fikri Eka; Tobirin, Tobirin; Ali Rokhman (HM Publisher, 2024)
E-government has become a global initiative to improve public services and citizen participation. Social media offers an interactive platform that has the potential to strengthen e-government implementation. This research aims to quantify the effectiveness of social media in various aspects of e-government through meta-analysis. A comprehensive literature search was conducted on Scopus, Web of Science, and Google Scholar for quantitative studies published between 2018-2024. Inclusion criteria included studies that measured the impact of social media on citizen participation, transparency, collaboration, or public trust in an e-government context. Data were extracted and effect sizes were calculated for each study. Meta-analysis was performed using a random effects model. Of the 40 studies that met the criteria (N = 22,698), meta-analysis showed that social media had a moderate to large positive effect on e-government implementation. The largest effect size was seen for transparency (0.51, 95% CI: 0.33-0.70), followed by community participation (0.47, 95% CI: 0.38-0.55), public trust (0.48, 95% CI: 0.40-0.57), and collaboration (0.45, 95% CI: 0.37-0.52). Subgroup analysis revealed that Facebook was the most effective platform, especially in increasing participation. The effects of social media tend to be stronger in developing countries. Moderator analysis shows that the level of internet penetration and digital literacy do not significantly moderate the effects of social media. In conclusion, social media has proven to be an effective tool in improving e-government implementation, especially in the context of public participation and transparency. Governments are advised to strategically integrate social media into e-government initiatives, taking into account the type of platform and local context.